"FIVE STEP" AND "THREE STEP" METHODOLOGIES - Ismailov Bobur Takhirovich (Scholar Express Journal, 2022)
This article describes the problem of equal distribution of liquid in given containers using "5 step" and "3 step" methods.
Keywords: fluid; constructive problem; mathematical competence; method